- #1

strat468

- 7

- 1

- TL;DR Summary
- augmenting a machine learning matrix

I have this equation which my professor has told me is correct so far.

##0 = -2*x^T(y-2(w*x+b))##

where

##x=\begin{bmatrix}

1 \\

2

\end{bmatrix}##

##y = 6##

##w =

\begin{bmatrix}

w1 & w2

\end{bmatrix}

##

##b = [b1]##

He told me to then augment w and b into one matrix in order to solve for both w and b.

How on earth do I do that?

##0 = -2*x^T(y-2(w*x+b))##

where

##x=\begin{bmatrix}

1 \\

2

\end{bmatrix}##

##y = 6##

##w =

\begin{bmatrix}

w1 & w2

\end{bmatrix}

##

##b = [b1]##

He told me to then augment w and b into one matrix in order to solve for both w and b.

How on earth do I do that?

Last edited: